Peran Ekuitas Merek dalam Memediasi Bauran Promosi dengan Keputusan Pembelian - Dewantara, Andika Agus; Nurcahya, I Ketut (E-Jurnal Manajemen; Vol 6 No 8 (2017), 2017)
The purpose of this study is to determine the effect of brand equity in mediating the promotional mix with purchasing decisions on Samsung brand smartphone users. The research was conducted in Denpasar City. The number of samples taken is as many as 100 respondents with purposive sampling method. Data collection is done by filling out a questionnaire measured by Likert scale. Analysis technique used in this research is path analysis (path analysis) and test of sobel. Based on the results of the study it was found that the promotion mix has a positive and significant influence on brand equity and purchasing decisions, brand equity has a positive and significant influence on purchasing decisions, and brand equity plays a role in mediating the influence of promotional mix on purchasing decisions.